Learning systemic management practice - Shaw, Corrinne (Department of Mechanical Engineering, 2014)
Systems thinking has been proposed as an answer to the question of how management practitioners can best equip themselves to tackle the complexity of management practice. As a body of work intended to transcend disciplinary silos, systems thinking pursues the ideal of generating comprehensive descriptions of real situations. It seeks to do this by embracing a variety of systems approaches and ideas to explain patterns and hypothesise causes of observable empirical events. As systems thinking is a diverse field, there are many knowledge areas and perspectives available to programme designers to facilitate teaching and the learning of systems thinking for management practice. The purpose of this study is to examine students' experience of learning events in the context of an interdisciplinary course designed for the development of management practice through systems thinking. Data was collected from three cohorts of students by observing lectures and class-based group work; and conducting interviews using conversational repertory grid techniques. The interview responses were analysed using grounded theory principles. Based on the findings derived from this qualitative analysis, the process of learning of systems thinking is outlined as a practice involving the selection and interpretation of events which evolve from the starting out phase, where students become interested in learning, and then outlines progress through the phases of assimilation and, changes in knowledge, culminating in more complex learning phases described as integration and adaptation. The synthesis of these phenomena as a theory provided an answer to the primary research objective of investigating how students experience learning events designed to develop systemic management practice. Critical realism, following Bhaskar's philosophy, is used to frame explanations to extend the grounded theory analysis, seeking to account for generative mechanisms that enable and constrain student experience with respect to systems thinking development. As a secondary contribution, this informed the identification of possible mechanisms and emergent properties at the level of the course through an analytical separation of the academic and work environments. These included the discourse of the context of application, academic discourse and professional identity. In combination, these findings make a contribution to understanding the learning of systemic management practice. In addition, applications for this research are suggested for educators, managers and organisations. These applications include: 1) a framework to help educators design meaningful experiences for learners; 2) a basis for understanding what constitutes systemic management practice and explaining differential development; 3) establishment of a basis for understanding what is needed for organisations to support the development of systemic management practice.